1997
DOI: 10.1093/humrep/12.2.220
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment transvaginal ultrasound examination predicts ovarian responsiveness to gonadotrophins in in-vitro fertilization

Abstract: The objective of this study was to determine the predictive value of the number of follicles seen by transvaginal ultrasound before gonadotrophin stimulation on the ovarian responsiveness of 166 infertile women undergoing in-vitro fertilization (IVF) treatment. The main variables were patient age, ovarian volume and number of ovarian follicles measuring 2-5 mm on transvaginal ultrasound before gonadotrophin stimulation. Based on the sum of ovarian follicles in both ovaries the patients were divided into three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
97
0
13

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(117 citation statements)
references
References 19 publications
7
97
0
13
Order By: Relevance
“…Inhibin B, a direct product of granulosa cells which might indicate the number of developing follicles, has been suggested as a direct biochemical marker of ovarian reserve (12,24). Recently, transvaginal ultrasound measurement of early follicular phase ovarian antral follicle counts and ovarian volume has been used to predict the response to ovulation induction in infertile women (14,15). To our knowledge, this is the first study designed to compare both hormonal and ultrasound parameters of ovarian reserve with basal and CC induced inhibin B concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibin B, a direct product of granulosa cells which might indicate the number of developing follicles, has been suggested as a direct biochemical marker of ovarian reserve (12,24). Recently, transvaginal ultrasound measurement of early follicular phase ovarian antral follicle counts and ovarian volume has been used to predict the response to ovulation induction in infertile women (14,15). To our knowledge, this is the first study designed to compare both hormonal and ultrasound parameters of ovarian reserve with basal and CC induced inhibin B concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that antral follicle counts and age were better measures than ovarian volume and hormones for predicting pregnancy in IVF. Others also found that number of antral follicles was related to age, number of oocytes retrieved, and cycle cancellations (14)(15)(16)33,34). Nevertheless, the general trend in the literature is such that age is an independent parameter in predicting pregnancy, certainly better than ultrasound and hormonal tests of ovarian reserve (21,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomas et al examined the predictive value of early-follicular-phase antral follicle count (AFC) detected by ultrasound (20). They found that the number of baseline follicles strongly correlated with the number of recovered oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors have been examined as prognostic markers related to the ovarian response to gonadotropin administration, including age [37], hormones such as follicle-stimulating hormone (FSH) [29], estradiol (E2) [18], inhibin B [24] and anti-Müllerian hormone [24,25], smoking [9], and sonographic indices of ovarian reserve such as ovarian volume, antral follicle count and ovarian blood flow [16,32,33]. Furthermore, certain predictive models of ovarian response have been developed, but they have modest accuracy and limited clinical use, because of high intra-and inter-individual variability [8] .…”
Section: Introductionmentioning
confidence: 99%